2014
DOI: 10.1186/1472-684x-13-24
|View full text |Cite
|
Sign up to set email alerts
|

Case conferences between general practitioners and specialist teams to plan end of life care of people with end stage heart failure and lung disease: an exploratory pilot study

Abstract: BackgroundMost people die of non-malignant disease, but most patients of specialist palliative care services have cancer. Adequate end of life care for people with non-malignant disease requires acknowledgement of their limited prognosis and appropriate care planning. Case conferences between specialist palliative care services and GPs improve outcomes in cancer-based populations. We report a pilot study of case conferences between the patient’s GP and specialist staff to facilitate care planning for people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 15 publications
1
87
0
Order By: Relevance
“…Of these studies, 7 did not include outcomes data for patients who were SQ- [14][15][16][17][18][19]36 that were confirmed in the publication [15][16][17][18]36 or after contact with study authors. 14,19 In 3 studies, the SQ was used only to predict 7-and/or 30-day mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 7 did not include outcomes data for patients who were SQ- [14][15][16][17][18][19]36 that were confirmed in the publication [15][16][17][18]36 or after contact with study authors. 14,19 In 3 studies, the SQ was used only to predict 7-and/or 30-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 7 did not include outcomes data for patients who were SQ- [14][15][16][17][18][19]36 that were confirmed in the publication [15][16][17][18]36 or after contact with study authors. 14,19 In 3 studies, the SQ was used only to predict 7-and/or 30-day mortality. 29,37,38 Sixteen remaining studies of SQ to predict death met inclusion criteria 1,[20][21][22][23][24][25][26][27][28][30][31][32][33][34][35] (Table 1) and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although little quantitative work has been completed in GP engagement in the integration of primary and secondary services in the provision of palliative care, studies showed a significant decrease in number of hospital admissions (p=0.0069; p=0.001) 2 22 23. Case conferences and shared care were both effective in reducing hospitalisations and in significantly (p<0.05) reducing the length of hospital stay 22 23.…”
Section: Resultsmentioning
confidence: 99%
“…Although little quantitative work has been completed in GP engagement in the integration of primary and secondary services in the provision of palliative care, studies showed a significant decrease in number of hospital admissions (p=0.0069; p=0.001) 2 22 23. Case conferences and shared care were both effective in reducing hospitalisations and in significantly (p<0.05) reducing the length of hospital stay 22 23. There was some evidence that patient functional status as measured by the Australian-modified Karnofsky Performance Scale (AKPS) was better maintained by patients receiving integrated care when performance status had already declined below a score of 70 (p=0.0425) 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation